Selective Electrical Stimulation of the Auditory Nerve Activates a Pathway Specialized for High Temporal Acuity - Middlebrooks, John C. (Society for Neuroscience, 2010)
Deaf people who use cochlear implants show surprisingly poor sensitivity to the temporal fine structure of sounds. One possible reason is that conventional cochlear implants cannot activate selectively the auditory-nerve fibers having low characteristic frequencies (CFs), which, in normal hearing, phase lock to stimulus fine structure. Recently, we tested in animals an alternative mode of auditory prosthesis using penetrating auditory-nerve electrodes that permit frequency-specific excitation in all frequency regions. We present here measures of temporal transmission through the auditory brainstem, from pulse trains presented with various auditory-nerve electrodes to phase-locked activity of neurons in the central nucleus of the inferior colliculus (ICC). On average, intraneural stimulation resulted in significant ICC phase locking at higher pulse rates (i.e., higher “limiting rates”) than did cochlear-implant stimulation. That could be attributed, however, to the larger percentage of low-CF neurons activated selectively by intraneural stimulation. Most ICC neurons with limiting rates >500 pulses per second had CFs <1.5 kHz, whereas neurons with lower limiting rates tended to have higher CFs. High limiting rates also correlated strongly with short first-spike latencies. It follows that short latencies correlated significantly with low CFs, opposite to the correlation observed with acoustical stimulation. These electrical-stimulation results reveal a high-temporal-acuity brainstem pathway characterized by low CFs, short latencies, and high-fidelity transmission of periodic stimulation. Frequency-specific stimulation of that pathway by intraneural stimulation might improve temporal acuity in human users of a future auditory prosthesis, which in turn might improve musical pitch perception and speech reception in noise.